U.S. Navy employment options for unmanned surface vehicles (USVs) - Savitz, Scott; Blickstein, Irv, 1939-; Buryk, Peter; Button, Robert W.; DeLuca, Paul; Dryden, James A.; Mastbaum, Jason; Osburg, Jan; Padilla, Philip; Potter, Amy; Price, Carter C.; Thrall, Lloyd; et al. (RAND, 2013)
This report assesses in what ways and to what degree unmanned surface vehicles (USVs) are suitable for supporting U.S. Navy missions and functions. It briefly characterizes the current and emerging USV marketplaces to provide a baseline for near-term capabilities, describes USV concepts of employment to support diverse U.S. Navy missions and functions, and evaluates these concepts of employment to identify specific missions and functions for which they are highly suitable. USVs offer several particular strengths relative to other platforms, including the ability to interact both above and below the waterline, enabling them to serve as critical nodes for cross-domain networks. They also have potentially longer endurance, larger payloads, and higher power outputs than comparably sized unmanned air or undersea vehicles. Additionally, their greater risk tolerance compared with manned systems makes them desirable platforms for overcoming adversaries' anti-access and area-denial measures. These strengths make USVs particularly suitable for missions such as characterizing the physical environment, observation and collection regarding adversaries, mine warfare, military deception/information operations/electronic warfare, defense against small boats, testing and training, search and rescue, and the support of other unmanned vehicles. However, USVs need advanced autonomy and assured communications to complete complex missions, as well as any missions in complex environments. Autonomous seakeeping and maritime traffic avoidance are USV-specific capabilities that likely need to be developed with U.S. Navy involvement. Also, optional manning and payload modularity can enhance the desirability of USV programs.